Role of the biochar modified with ZnCl2 and FeCl3 on the electrochemical degradation of nitrobenzene. (July 2021) - Liu, Qiang; Jiang, Shiqi; Su, Xintong; Zhang, Xiaolei; Cao, Weimin; Xu, Yunfeng
Abstract: The Zn/Fe-modified biochar on nitrobenzene (NB) removal during the electrolysis was investigated in this study. Both the Fe and Zn-modified biochar enhanced the NB adsorption compared with the un-modified biochar due to their greater specific surface area and more abundant surface function groups, respectively. The electrolysis under 2–11 V with the assist of both Fe/Zn-modified biochar achieved effective NB removal (>93%). The removal rate under 2 V using Zn/Fe-modified biochar (∼94%) was higher than that of the un-modified biochar (∼80%), whereas the removal was similar for those under 5, 8 and 11 V. The NB removal under 2 and 5 V was attributed to both adsorption and electrochemical decomposition of NB molecules. Electrolysis under 5 V by Fe-modified biochar had a higher degree of NB mineralisation than that using un-modified and Zn-modified biochar. This was likely that the Fe-modified biochar exhibited higher electrocatalytic properties, facilitating the further NB mineralisation. The ∙OH played significant roles in the degradation of NB by Fe-modified and un-modified biochar but did not significantly participated for the test using Zn-modified biochar. This was possibly because the Zn-modified biochar could adsorb greater amounts of ∙OH into the inner pores of Zn-modified biochar via its greater porosity and specific surface area, which may prevent the contact between ∙OH and NB molecules. Highlights: The role of Zn/Fe-modified biochar on NB electrolysis was investigated. Fe and Zn-modification increased the pecific surface area and functional groups. Fe and Zn-modified biochar enhanced the NB adsorption and electrolysis. Fe-modified biochar gave higher degree of NB mineralisation under 5 V.